Low Iodine Diet for Preparation for Radioactive Iodine Therapy in Differentiated Thyroid Carcinoma in Korea - Jae Hoon Chung (Endocrinology and Metabolism, 2013)
Preparation for radioactive iodine (RAI) therapy includes an increased serum thyroid stimulating hormone level and a low iodine diet (LID). Because of extremely high iodine intake, some physicians have advocated a more stringent LID for greater than 2 weeks in Korean patients with thyroid cancer prior to RAI therapy; however, it is very difficult to maintain a stringent LID for a longer period of time. According to recent reports in Korea, a nonstringent, simple LID for only 1 week might be enough prior to RAI therapy, if the patients can be educated intensively by specially trained staff. The measurement of simple urinary iodine concentration (UIC; µg/L) may underestimate daily iodine excretion in patients with a urinary volume of more than 1 L/day and can also be affected by dilution status. Simple UIC had a weaker correlation than the iodine/creatinine (I/Cr) ratio. Therefore, the urinary I/Cr ratio can replace 24-hour urine iodine excretion instead of simple UIC, although it may overestimate iodine intake in patients with malnutrition or poor muscle mass. The measurement of serum iodine level might be useful as an adjunct parameter for assessing LID preparation, but its sensitivity and specificity were relatively low compared to the urinary I/Cr ratio.